Brain Abscess in the Current Decade (2010–2019) in India—A Review - Ravikumar, R.; John, Daisy Vanitha (Indian Journal of Neurosurgery, 2021)
Brain abscess outcomes have improved in recent years due to advancements in cranial imaging, microbiological techniques, minimally invasive neurosurgical procedures, and effective antibiotic treatments. However, the incidence of brain abscess remains unchanged in developing countries. We searched PubMed and Google Scholar for references using the key words “brain abscess” and “India” and reviewed both retrospective and prospective studies published in peer-reviewed journals in the current decade to understand the present status. The review shows that the patients’ ages, the predominance of male patients, the symptoms and locations of brain abscesses, and the types of bacteria associated with them have remained unchanged over the past decade. The most common predisposing condition in recent years has been chronic suppurative otitis media with a mortality rate of 7 to 10%. Middle ear infection is often neglected and not treated aggressively in Asian countries. It requires multidisciplinary treatment strategies to address the primary source of infection and better health awareness to prevent the development of brain abscess.
Keywords: brain abscess; chronic suppurative otitis media (CSOM); prevention